Colonial legacies in Chicana/o literature and culture : looking through the kaleidoscope - Fonseca-Chávez, Vanessa, 1982- (University of Arizona Press, 2020)
"Colonial Legacies in Chicana/o Literature and Culture traces the development of Chicana/o literature and cultural production from the Spanish colonial period to the present. In doing so, it challenges us to look critically at how we simultaneously embody colonial constructs and challenge their legacies"--